2019
DOI: 10.29252/ibj.23.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Neural Network in miRNA Biomarker Selection and Precise Diagnosis of Colorectal Cancer

Abstract: Background:The early diagnosis of colorectal cancer (CRC) is associated with improved survival rates, and development of novel non-invasive, sensitive, and specific diagnostic tests is highly demanded. The objective of this paper was to identify commonly circulating microRNA (miRNA) biomarkers for use in CRC diagnosis. Methods: An artificial neural network (ANN) model was proposed in this work. Among miRNAs retrieved from the Gene Expression Omnibus dataset, four miRNAs with the best miRNA score were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…The SVM classification model demonstrated 85% sensitivity and 90% specificity. Afshar et al [19] proposed an artificial neural network model, which accurately classified the sample data into cancerous and non-cancerous by screening four CRC-specific miRNAs retrieved from the Gene Expression Omnibus (GEO) database. In addition, Xuan et al [20] suggested using a dual CNN prediction model for discovering potential disease-related miRNAs.…”
Section: Artificial Intelligence Colorectal Cancer and Genomicsmentioning
confidence: 99%
“…The SVM classification model demonstrated 85% sensitivity and 90% specificity. Afshar et al [19] proposed an artificial neural network model, which accurately classified the sample data into cancerous and non-cancerous by screening four CRC-specific miRNAs retrieved from the Gene Expression Omnibus (GEO) database. In addition, Xuan et al [20] suggested using a dual CNN prediction model for discovering potential disease-related miRNAs.…”
Section: Artificial Intelligence Colorectal Cancer and Genomicsmentioning
confidence: 99%
“…Recurrent neural network (RNN) has memory, parameter sharing, and Turing completeness, and it demonstrates superb capabilities in learning nonlinear characteristics of sequences. e combination of RNN and convolutional neural network (CNN) can extract image features frame by frame, thereby saving manpower and improving accuracy [8]. DC is used to solve the problem in image segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the fourth life-threatening cancer in the world, which is caused by the uncontrollable division and abnormal growth of the colorectal cells (1)(2)(3). Like all other types of cancer, surgical resection, chemotherapy, and radiotherapy are the main treatment options in clinical practice (4,5).…”
Section: Introductionmentioning
confidence: 99%